Digital literacy of undergraduate students using assessment for learningin applied computer course during the COVID-19 pandemic (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research is the study of Digital literacy of undergraduate students using assessment for learning in applied computer course during the COVID-19 pandemic. This research is the study of Digital Literacy (DL) of undergraduate students using assessment for learning in applied computer course during the COVID-19pandemic. To develop an assessment for learning in applied computer course. To study digital literacy knowledge of students in the course in applied computer course, online course. The population consist of 46 persons. Undergraduate student's bachelor of Science in Food Technology Applied Computing in Mahidol University. Statistics used for this research. Because it uses the entire population in research. The statistics used consisted of Cronbach Alpha coefficient, Frequency, Mean, Standard deviations were used to analyze the data. The investigators found that to develop an assessment for learning in applied computer course. Assessment for learningcan improve undergraduate students' ability to use DL and DL knowledge of students in the course. The results showed that access, analyze, create, evaluateof those who have improved by using such an assessment model and the development score (DS): 73.27% was learners have a high level of development.